School and social transformation: Another view of the educational organization. - Rodríguez Díaz, Rodiel (Márgenes, Revista de Educación de la Universidad de Málaga, 2024)
Testifying to the academic work in biographical narratives, carried out by the authors, the researcher Juan Bautista Martínez Rodríguez, presents in the prologue the transversal axes of the work: a) the practice of narrative research, b) the historical, epistemological, reflective framework institutional and the disruptive sense, and c) the aspiration for social transformation in educational centers (p.9), in consideration of disruptive organizations (p.16) In the prelude to the introduction, the origin of the institution, the school and its organization in the context of modernity is described, a situation that achieves the current mold of society. Consequently, the work distances itself from “the functionalist and administrative view” (p.19) that prevails in school organization, emphasizing what is emerging and invisible, in order to question what ideas of an educational institution does the school act on? (p. 20) Now, the book, constructed in six chapters and a postface, exposes in depth the DNA of the school organization, the alternate view of the school and its social transformation.